2018
DOI: 10.1088/1748-0221/13/10/p10028
|View full text |Cite
|
Sign up to set email alerts
|

A compact, high resolution tracker for cosmic ray muon scattering tomography using semiconductor sensors

Abstract: A semiconductor tracker for muon scattering tomography is presented. The tracker contains silicon strip sensors with an 80 μm pitch, precision mechanics and integrated cooling. The electronic readout of the sensors is performed by a scalable, inexpensive, flexible, FPGA-based system, which is demonstrated to achieve an event rate of 30 kHz. The tracker performance is compared with a Geant4 simulation. A scattering angle resolution compatible with 1.5 mrad at the 4 GeV average cosmic ray muon en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…14). These were originally developed for a test system of the LHCb RICH upgrade at Cambridge University and were later used for cosmic muon tomography with eight spare SCT modules [27].…”
Section: B Module Selection and Quality Assurancementioning
confidence: 99%
“…14). These were originally developed for a test system of the LHCb RICH upgrade at Cambridge University and were later used for cosmic muon tomography with eight spare SCT modules [27].…”
Section: B Module Selection and Quality Assurancementioning
confidence: 99%
“…The prompt (emitted without time delay) Cherenkov radiation and focusing geometry of the RICH detectors results in an excellent intrinsic time resolution. The signal from a single proton-proton interaction fits within a window of 50 ps in RICH 1 and 500 ps in RICH 2 [7]. The larger time for RICH 2 is explained by the size and position of the detector.…”
Section: Using Timing For Background Reductionmentioning
confidence: 94%
“…With timing information, it is possible to select photon signals in a well-defined ToA interval and reduce out-of-time background by applying a time gate to the front-end electronics. The FPGA in the read-out system samples the CLARO signals at 320 MHz and applies the time gate to a specific input pattern [7]. Beam tests at the CERN SPS have shown that using a time gate of 6.25 ns can increase the signal-to-noise ratio by a factor of three to four, thus improving the performance of the RICH pattern recognition algorithms.…”
Section: Timing For Background Reductionmentioning
confidence: 99%